Attitudes, beliefs and perception of menstruation related socio-cultural practices and menstrual hygiene management among in-school adolescent girls in Cross River State, Nigeria: Adolescents’ menstrual hygiene beliefs and practices (African Journal of Biomedical Research, 2021)
Background: Menstruation and its management in developing countries including Nigeria are often shrouded in inhibitory cultural myths, taboos and stigma. The study examined the perceptions of adolescent in-school girls about the teaching of menstruation and sexuality education in schools, socio-cultural practices associated with menstruation and how they managed menstruation was assessed.Methods: A cross-sectional questionnaire-based survey was carried out among 1006 randomly selected urban and rural-based adolescent schoolgirls from both public and private secondary schools in Cross River State, Nigeria.  Results:  Most (72.8%) of the respondents supported discussions about menstruation and the teaching of sexuality education in schools. Over 70% of the respondents were opposed to the prohibitive practices associated with menstruation, 80% of the girls used sanitary pads as menstrual absorbents.    Conclusions:  The teaching of contextual sexuality education in Nigerian schools to address existing myths, beliefs and misconceptions about menstruation and its management should be encouraged and sustained.